Implementation of the Card Sort Method for Hajj Material in Fiqh Learning - Anita Miqnaul Lailiyah; Romelah; Dina Mardiana (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
Today, there are still many educators who still need to improve in carrying out the learning process. In this case, there is a reset problem, which lies in the ineffectiveness of the learning process caused by passive students. So, this research provides a solution using the card sort method in fiqh learning. This study aimed to analyze the card sort understanding technique in Batu's tsanawiyah madrasah. This study uses the theory of Melvin L. Siberman that the card sort method has potential and advantages related to student active learning. This research uses a qualitative approach with a case study type of research. Data collection using observation, interview and documentation techniques. Next, the data was analyzed using descriptive data analysis. This study concluded that using the card-sort learning method of Hajj material positively impacts learning activities. Applying the card sort method can increase students' creative abilities and understanding of Hajj material.